Pengembangan Madrasah dengan Modal Sosial - Taiyudin Subki (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: The condition of education in Indonesia until now is still quite alarming. Various efforts to increase and development continue to be done, but the result are still not in accordance with social hope. Modal public in the field of education (madrasah) is one that will be introduced as anew approach in education, particularly in the madrasa development that require proper handling, clear, tranparent effective, efficient, and requires a container that meets to set a benchmark for the succes and failure in implementation. Keywords: Social capital, madrasah, Islamic school.